Analysis of the Earth Fixed Beam Duration in the LEO - Baik, Jong Soo; Kim, Jae Hyun (International Conference on Information Networking, 2021)
In this paper, we analyze the earth fixed beam of low earth orbit (LEO) satellite, which is currently undergoing standardization. Earth fixed beam LEO communicates with one coverage area for a certain period of time and moves beam after a certain period of time to communicate with the other. We check the tendency of cell throughput and analyze reference signal received power (RSRP), which is an indicator of handover and cell reselection, according to this time period.
Keywords: Cell reselection; Coverage area; Earth orbits; Fixed beam; Hand over; Low earth orbit satellites; Received power; Reference signals; Time-periods